A qualitative study of self-evaluation of junior doctor performance: is perceived 'safeness' a more useful metric than confidence and competence?. Issue 11 (4th November 2015) - Roland, Damian; Matheson, David; Coats, Timothy; Martin, Graham
Abstract : Objectives: The terms confidence and competence have been poorly defined and are often misused by junior doctors. Given safe practice relies on healthcare professionals being aware of their own skill sets improving self-assessment of confidence and competence is important. The aim of this work was to explore junior doctors' understanding of how they perceive their own performance in respect of managing feverish children in an emergency department. Setting: A children's emergency department in a tertiary hospital in the East Midlands, UK. Participants: 22 Junior doctors volunteered to undertake focus groups via a meta-planning methodology over 2 years (14 participants in the first year and 8 in the second). Results: Although doctors were aware of the difference between confidence and competence they were not able to distinguish between them in practical terms. The feeling of being 'safe' emerged as a term in which there was a shared understanding compared to reported confidence and competence. Conclusions: A perception of 'safeness' is a concept that may aid self-evaluation and we present a matrix that might be used by supervisors and educators to examine this and its relationship with confidence and competence.